2012
DOI: 10.1007/s10711-012-9802-5
|View full text |Cite
|
Sign up to set email alerts
|

A finite subdivision rule for the n-dimensional torus

Abstract: Abstract. Cannon, Floyd, and Parry have studied subdivisions of the 2-sphere extensively, especially those corresponding to 3-manifolds, in an attempt to prove Cannon's conjecture. There has been a recent interest in generalizing some of their tools, such as extremal length, to higher dimensions. We define finite subdivision rules of dimension n, and find an n − 1-dimensional finite subdivision rule for the n-dimensional torus, using a well-known simplicial decomposition of the hypercube.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The most commonly studied type of subdivision rule is a finite subdivision rule [2,27]. Intuitively, a finite subdivision rule takes a CW-complex where each cell is labelled and refines each cell into finitely many smaller labelled cells according to a recursive rule.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly studied type of subdivision rule is a finite subdivision rule [2,27]. Intuitively, a finite subdivision rule takes a CW-complex where each cell is labelled and refines each cell into finitely many smaller labelled cells according to a recursive rule.…”
Section: Definitionmentioning
confidence: 99%
“…There are numerous explicit examples of finite subdivision rules on the 2-sphere that represent hyperbolic 3-manifolds, as well as subdivision rules representing hyperbolic knot complements [2,[25][26][27].…”
Section: Theorem 10 Let R Be a Subdivision Rule And Let X Be An R-comentioning
confidence: 99%
“…In this paper, we find subdivision rules for RAAG's that subdivide or act on the n-sphere. In [23], we defined a subdivision rule in higher dimensions in a way analogous to subdivision rules in dimension 2. We repeat that definition here.…”
Section: Formal Definition Of a Subdivision Rulementioning
confidence: 99%
“…Cannon and Swenson and shown that two-dimensional subdivision rules for a three-dimensional hyperbolic manifold group contain enough information to reconstruct the group itself [2,5]. This was later generalized to show that many groups can be associated to a subdivision rule of some dimension, and that these subdivision rules [9,8]:…”
Section: Introductionmentioning
confidence: 99%